2010
DOI: 10.1007/s10450-010-9289-z
|View full text |Cite
|
Sign up to set email alerts
|

A novel and consistent method (TriPOD) to characterize an arbitrary porous solid for its accessible volume, accessible geometrical surface area and accessible pore size

Abstract: We present an improved Monte Carlo integration method to calculate the accessible pore size distribution of a porous solid having known configuration of solid atoms. The pore size distribution obtained with the present method is consistent with the accessible volume and the accessible geometric surface area presented in previous publications (Do and Do, in J. Colloid Interface Sci. 316 (2): 317-330, 2007; Do et al. in Adsorpt. J., 2010). The accessible volume, accessible geometrical surface area and the pore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
(39 reference statements)
0
5
0
Order By: Relevance
“…In a subsequent article, this method was further improved and described in more detail by the same group and also used to analyze the APSD of IRMOF-1, IRMOF-10, and IRMOF-16. Figure shows an example for the results obtained for IRMOF-1 with argon as the probe particle.…”
Section: Development Of Computational Methods and Concepts For Mofsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a subsequent article, this method was further improved and described in more detail by the same group and also used to analyze the APSD of IRMOF-1, IRMOF-10, and IRMOF-16. Figure shows an example for the results obtained for IRMOF-1 with argon as the probe particle.…”
Section: Development Of Computational Methods and Concepts For Mofsmentioning
confidence: 99%
“…By including the combined collision diameter (3.1 Å) between the argon and the hydrogen atom in the material, Do and co-workers found that the accessible pore sizes (11.8 and 15.4 Å, respectively) are in good agreement with TEM image analysis. It should be noted that they also presented the procedure for calculating the accessible geometrical surface area, which is defined as the area of the boundary of the accessible volume …”
Section: Development Of Computational Methods and Concepts For Mofsmentioning
confidence: 99%
See 1 more Smart Citation
“…The S/V boundary is one that passes through the centres of solid atoms in the innermost layer. The S/A is the boundary determined by helium expansion, and the boundary of zero SF potential is the one separating the accessible volume and the inaccessible volume (Herrera et al 2010b) because the pore size of a given point X in the accessible pore's volume is defined as the size of the largest sphere that accommodates in such a way that the sphere rests on surface of zero potential of the three closest solid atoms to the point X (Fig. 5).…”
Section: Accessible and Inaccessible Volumesmentioning
confidence: 99%
“…The accessible void volume was then determined using Monte Carlo integration. Do and coauthors also defined an accessible pore size as the diameter of the largest sphere than can be put inside the accessible volume using a Tri-POD method. They pointed out that accessible pore radius and accessible pore volume vary for gas molecules with different LJ parameters.…”
Section: Introductionmentioning
confidence: 99%